2013
DOI: 10.1016/j.scr.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term repopulating hematopoietic stem cells and “side population” in human steady state peripheral blood

Abstract: This report brings the first experimental evidence for the presence of long-term (LT) repopulating hematopoietic stem cells (HSCs) and Side Population (SP) cells within human steady state peripheral blood CD34(+) cells. Ex vivo culture, which reveals the LT-HSC, also increases short-term (ST) HSC engraftment capacity and SP cell number (as well as the SP subpopulations defined on the basis of CD38, CD90 and CD133 expression) which are very low in freshly isolated cells. Thus, ex vivo incubation either allows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…However, because of the small size further experiments are required, including independent replications, to truly validate the potential for EMS to activate HSCs. Nevertheless, our finding indicates that the EMS activates the migratory capabilities of the steady state HSCs of healthy participants, 62 independently of vessel injuries and is sufficient for extravasation. The treatment is acting rapidly, well tolerated, and inexpensive.…”
Section: Discussionmentioning
confidence: 63%
“…However, because of the small size further experiments are required, including independent replications, to truly validate the potential for EMS to activate HSCs. Nevertheless, our finding indicates that the EMS activates the migratory capabilities of the steady state HSCs of healthy participants, 62 independently of vessel injuries and is sufficient for extravasation. The treatment is acting rapidly, well tolerated, and inexpensive.…”
Section: Discussionmentioning
confidence: 63%
“…Murine studies demonstrated HSC migration to ectopic niches via the circulation (Christensen et al, 2004;Wright et al, 2001). HSCs were detected in the blood of 12-to 18-week-old human fetuses (Gallacher et al, 2000), and long-term repopulating HSCs were demonstrated in adult human steady-state peripheral blood (Bourdieu et al, 2017;Brunet de la Grange et al, 2013). We now demonstrate the turnover of ''ectopic'' niche HSPCs from the circulating pool in humans.…”
Section: (Legend Continued On Next Page)mentioning
confidence: 60%
“…Side population (SP) cells were identified in both preterm and term CB as previously described [ 21 ]. Mononuclear cells were resuspended at 10 6 cells/mL in warmed staining buffer [DMEM supplemented with 2% fetal calf serum (FCS)] and incubated with 5 μM Dye Cycle Violet (DCV; Molecular Probes Invitrogen Inc.,) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%